Bibliometric analysis of publications related to the production of furfural from lignocellulosic biomass in the period 2015-2021 - Butrica Ferre, Valerie Noemi (2023)
The objective of this research article is to present the results of the literature review of furfural production, to determine the optimal production conditions, potential uses and relevance for the scientific community between 2016 to 2021. To analyze the problem, 2-time horizons were defined, from 2015 - 2018 and 2019 - 2021 with which a systematic mapping was performed. For the results and discussion of the findings, the 11 most relevant articles of the total collected were chosen, considering the number of citations per article and their percentile of prominence from databases such as Scopus and Web of Science. Then, the VOSviewer software was used to generate the co-occurrence network of the topics present to visualize the most relevant keywords for each year and in each database. Finally, the research work is concluded by commenting on the scope of furfural use in industries, the raw materials with the highest pentose content and the development of improvements in production to optimize furfural yield.